2018
DOI: 10.5005/jp-journals-10024-2232
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative Index in Invasive Tumor Front of Oral Squamous Cell Carcinoma: A Potential Prognostic Indicator

Abstract: Aim:The aim of the study was to evaluate the proliferative index (PI) at their invasive front of oral cancer and their association with Bryne's grades of oral squamous cell carcinoma (OSCC) and compare the PI with lymph node metastasis, site of involvement, and habits. Materials and methods:The Ki-67 antigen expression was immunohistochemically evaluated in a total of 102 cases that included the histopathologically diagnosed archival specimens of OSCCs. They were subdivided by Bryne's histopathological gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 22 publications
3
2
0
Order By: Relevance
“…Although most reviewed authors, Watanabe et al , Gonzalez-Moles et al , Lopes et al Cortegoso et al did not find statistically significant relation between Ki-67 expression and nodal status of the patients which was in concurrence with our results, some papers showed that the relation in this respect is significant ( 8 , 10 , 34 , 40 , 42 , 47 ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Although most reviewed authors, Watanabe et al , Gonzalez-Moles et al , Lopes et al Cortegoso et al did not find statistically significant relation between Ki-67 expression and nodal status of the patients which was in concurrence with our results, some papers showed that the relation in this respect is significant ( 8 , 10 , 34 , 40 , 42 , 47 ).…”
Section: Discussionsupporting
confidence: 90%
“…Our results did not confirm significant differences in Ki-67 expression when compared to the differentiation grade of the tumor (G). Consistent results were reported by Lopes et al , Watanabe et al , Guimarães et al , however, there were also convincing reports from Bhuyan et al , Verma et al , Gonzalez-Moles et al , Dragomir et al , Motta et al and Coutinho-Camillo et al who found significantly higher Ki-67 expression in poorly differentiated tumors ( 8 , 10 , 34 , 37 , 40 , 47 - 50 ).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The PHH3 antibody, recognized as a biomarker of cell proliferation and specific for cells in mitosis, has been little studied in comparison with other biomarkers of cell proliferation ( 25 ). In contrast, in OSCC, unlike the PHH3 antibody, one of the cell proliferation biomarkers that has been widely studied is Ki-67 ( 4 , 13 , 22 , 26 ). However, studies on the value of the expression of this biomarker in determining the survival of patients with OSCC have shown contradictory results ( 3 , 15 ).…”
Section: Discussionmentioning
confidence: 99%